Research on photovoltaic energy storage micro‐grid systems based on improved sliding mode control. Issue 3 (6th November 2022) - Fu, Changxin; Zhang, Lixin; Li, Huaisheng
Abstract: In islanded microgrid systems, PV power generation efficiency and energy loss of storage battery are the current research trends. Due to the intermittent and fluctuating characteristics of PV power generation, various loads connected to the DC microgrid system would also bring DC bus voltage low‐frequency fluctuations and other problems. In order to solve the above problems, an maximum power point tracking (MPPT) tracking strategy (sliding mode control based on squirrel search algorithm) is proposed in this study; meanwhile, a sliding mode control strategy based on an improved reaching law is designed. The components of the PV energy storage system and the control method are mainly focused on, and the PV energy storage system is optimized by improving the sliding mode control. The proposed control algorithm is verified and analyzed by MATLAB/Simulink simulation platform. Compared with the double integral sliding mode control algorithm MPPT tracking case, sliding mode control based on squirrel search algorithm shows excellent performance (short response time, good tracking maximum power point effect etc.). In addition, the sliding mode control based on the proposed reaching law reduces the system jitter, and effectively reduces jitter and vibration of the PV energy storage battery.